Activation of cannabinoid receptor 2 attenuates Angiotensin II-induced atrial fibrillation via a potential NOX/CaMKII mechanism - Xu, Dengyue; Xu, Chennian; Xue, Xiaodong; Xu, Yinli; Zhao, Jikai; Huang, Tao; Wang, Zhishang; Zhao, Qiusheng; Zhou, Zijun; Huang, Yuting; Yu, Liming; Wang, Huishan (Frontiers in Cardiovascular Medicine, 2022)
Background: Atrial fibrillation (AF) is the most frequent arrythmia managed in clinical practice. Several mechanisms have been proposed to contribute to the occurrence and persistence of AF, in which oxidative stress plays a nonnegligible role. The endocannabinoid system (ECS) is involved in a variety physiological and pathological processes. Cannabinoid receptor 1 (CB1R) and cannabinoid receptor 2 (CB2R) are expressed in the heart, and studies have shown that activating CB2R has a protective effect on the myocardium. However, the role of CB2R in AF is unknown. Methods: Angiotensin II (Ang II)-infused mice were treated with the CB2R agonist AM1241 intraperitoneally for 21 days. Atrial structural remodeling, AF inducibility, electrical transmission, oxidative stress and fibrosis were measured in mice. Results: The susceptibility to AF and the level of oxidative stress were increased significantly in Ang II-infused mice. In addition, nicotinamide adenine dinucleotide phosphate oxidase 2 (NOX2), NOX4 and oxidized Ca2+/calmodulin-dependent protein kinase II (ox-CaMKII) were highly expressed. More importantly, treatment with AM1241 activated CB2R, resulting in a protective effect. Conclusions: The present study demonstrates that pharmacological activation of CB2R exerts a protective effect against AF via a potential NOX/CaMKII mechanism. CB2R is a potential therapeutic target for AF.